2017
DOI: 10.1039/c7ra06997a
|View full text |Cite
|
Sign up to set email alerts
|

Flexible piezocapacitive sensors based on wrinkled microstructures: toward low-cost fabrication of pressure sensors over large areas

Abstract: Wrinkled elastomeric templates prepared by stretching and releasing are utilized for demonstrating highly sensitive, simple, and low-cost piezocapacitive pressure sensors over large area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(42 citation statements)
references
References 31 publications
(47 reference statements)
2
38
0
Order By: Relevance
“…More importantly, micro-/nano-structure in the elastomeric electrode is thought to be a key element of sensor devices [21][22][23][24], providing faster response time, and higher sensitivity compared to the unstructured electrode [25,26]. Therefore, structured graphene-based sensors have potential to possess superior performance [27].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, micro-/nano-structure in the elastomeric electrode is thought to be a key element of sensor devices [21][22][23][24], providing faster response time, and higher sensitivity compared to the unstructured electrode [25,26]. Therefore, structured graphene-based sensors have potential to possess superior performance [27].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in recent years, a pressure sensor using polymer materials has received much attention among academics and industry due to its unique advantages, including low-temperature processing, low manufacturing costs, mechanical flexibility, and the potential to work in a large area [7,8,12,13,14,15,16,17,18,19,20,21,22,23]. These characteristics indicate the potential to construct the next generation of IoT (Internet of Things) sensing nodes, where the sensor is required to not only be low-power and low-cost, but also, be compatible with many surface types [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These characteristics indicate the potential to construct the next generation of IoT (Internet of Things) sensing nodes, where the sensor is required to not only be low-power and low-cost, but also, be compatible with many surface types [11,12]. Structurally, the sensor contains an active polymer material layer sandwiched between two electrodes [8,12,13,14,15,16,17,18,19,20,21,22,23]. Based on the physical phenomena of piezoresistivity, piezocapacity, and piezoelectricity, when the applied pressure changes, the resistance, capacitance, or electricity of the sandwiched layer varies, which, in turn, causes the output electrical signal of the device to change.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular structure used in capacitive e-skin is polydimethylsiloxane (PDMS)/Ecoflex dielectric layer sandwiched between two electrodes because of its easiness of preparation and simplicity of data acquisition. 9,10 Previous studies have shown that adding proper microstructures in the dielectric layer can effectively improve the sensitivity of the sensing unit, and different shapes and sizes of microstructure have a significant impact on it as well (flat, 11 trapezoidal, 12 half-cylinder, 13 and pyramids 14 ). However, most research investigated the sensing ability through experiments.…”
Section: Introductionmentioning
confidence: 99%